STRUCTURAL ANALYSIS OF INFLUENCING FACTORS FOR SUSTAINABILITY OF URBAN GREEN SPACES - Ihsani, Irfan; Kusmana, Cecep; Machfud; Pravitasari, Andrea Emma (Jurnal Infrastruktur, 2024)
Kota Depok, located in the western part of West Java Province, has experienced rapid growth over the past few decades. This growth occurred alongside intense urbanization, industrial development, and population increase. Apart from the positive impact of economic growth and infrastructure development, this rapid development causes environmental damage and loss of green open land. This can impact air, water, and soil quality and threaten environmental sustainability. This paper systematically tries to inventory the factors involved in urban green spaces' sustainability with a structural approach using Cross-Impact Matric Multiplication Applied to Classification (MICMAC) software. Of the 12 factors analyzed, five have a strong level of influence and low dependence, and 3 have a strong influence but have high reliance. These factors are 1) LU policy, 2) law enforcement, 3) environmental education, 4) stakeholder integrity, and 5) community involvement and participation, while 1) biodiversity conservation, 2) land value, and 3 ) environmental maintenance and protection is a factor that has a strong influence but is also highly dependent. Stakeholders can use the results of identifying these key factors as considerations for making decisions.